Inter And Intra-language Challenges In English Intonation Of Nigerian English Bilinguals: Implications For Learning - Akindele , Julianah; Oladipupo, Rotimi (The Journal of Studies in Language, Culture, and Society, 2024)
This study relies on acoustic evidence to investigate the English intonation usage of 20 NigE bilinguals from two universities in south-west, Nigeria. They produced validated utterances with varied meanings (e.g. protest, detached, interested, impressed, encouraging, bored, grateful, order, request and questioning) into speech recording devices. Their responses were converted to TextGrids in Praat and labelled for tone point tiers on which the pitch accent was labelled as L* or H* and the final pitch height as L% or H%. The findings reveal a preponderance of a simple fall tone even in contexts where other tones are expected. A rise was attested in polite requests, declarative questions and surprise, a little evidence of fall-rise was found in declarative questions, while a rise-fall was not attested at all. This suggests a paucity of bi-directional intonation tones in the speech of the participants and confirms their limitation in using intonation to communicate various shades of meaning. The study concludes that, despite the participants’ classroom exposure to the subject of intonation, they are not suitable models of intonation for Nigerian learners of English, and thus recommends that Nigerian learners should rely on technology-driven, non-enculturation sources of speech practice.